Enteric-coated budesonide for the induction and maintenance of remission of Crohn's disease in children. (3rd July 2017) - Cohen, Stanley A.; Aloi, Marina; Arumugam, Ramalingam; Baker, Robert; Bax, Kevin; Kierkuś, Jaroslaw; Koletzko, Sibylle; Lionetti, Paolo; Persson, Tore; Eklund, Stefan
Abstract: Objective: These studies evaluated the safety and efficacy of enteric-coated budesonide for the induction and maintenance of remission of mild-to-moderate Crohn's disease (CD) in children. Methods: The consecutive, multicenter, open-label, non-comparative studies enrolled patients aged 6–17 years. In the induction study, patients with active CD of the ileum and/or ascending colon received budesonide 9 mg or 6 mg once daily for 8 weeks; in the maintenance study, patients in remission received budesonide 6 mg once daily for 12 weeks. The primary objective was assessment of safety, including glucocorticosteroid-related side effects and serum cortisol levels. Efficacy was assessed using the Pediatric Crohn's Disease Activity Index (PCDAI), and health-related quality of life (HRQoL) using the IMPACT-III questionnaire. Results: In the induction study ( n  = 108), most adverse events were related to CD, commonly abdominal pain; possible glucocorticosteroid-related effects included acne and increased appetite but without significant weight gain. Subnormal morning cortisol levels were observed in 32 of 103 patients after 8 weeks. Budesonide reduced disease activity from baseline (mean ± standard deviation, 9.1 ± 8.5 vs. 19.1 ± 10.1, p  < .001) with 58.1% of patients reaching remission (PCDAI <10); HRQoL improved ( p  < .001). In the maintenance study ( n  = 50), mean disease activity worsened ( p  = .047) with HRQoL unchanged ( p  = .33). Conclusions: Budesonide treatment was generally well tolerated, although the potential for adrenal suppression was noted. Budesonide was effective for induction of remission in children with mild-to-moderate CD but not for maintaining remission (ClinicalTrials.gov identifiers: NCT01444092, NCT01453946).